The Role of Job Insecurity and Job Stress in Shaping Turnover Intentions: Insights from Employee Perspectives Banking in Jabodetabek - Kery Utami; Abdul Rajak Abdul Hadi; Yoko Tristiarto; Wahyudi Wahyudi (Garuda Prestasi Nusantara Consulting, 2024)
This study aims to analyze the influence of Job Insecurity and Job Stress on Turnover Intention among bankemployees in the Greater Jakarta area. In the context of the Job Demand-Resources theory, job uncertainty (JobInsecurity) and job stress (Job Stress) are considered factors that can affect employees' intentions to leave thecompany. The research method used was quantitative with a survey design, where data was obtained from 56employees working at several banks in Greater Jakarta. Data processing was carried out using SmartPLS 3.0, withthe T test to test the hypothesis and bootstrapping analysis to test the significance of the relationship between thevariables. The results of the study show that both Job Insecurity and Job Stress have a significant positive influenceon Turnover Intention. This research provides important insights for companies to manage job uncertainty andemployee stress to reduce turnover intention. In the practical aspect, companies are advised to introduce policies thatcan reduce uncertainty in work and provide better psychological support for employees, to prevent an increase inturnover intention that adversely affects the organization. The impact of this study on company managers is significant,as the management of job uncertainty and stress can affect employee retention and create a more productive workenvironment. HR managers need to be more aware of the factors that can increase turnover intention and designpolicies that emphasize job stability and employee well-being. The novelty of this study lies in the application of theJob Demand-Resources model in the context of banks in the Greater Jakarta area, as well as the use of SmartPLS 3.0to test the relationship between variables that contribute to the development of human resource theory and practice inthe banking industry